Spectral Observation of Solar Photosynthetically Active Radiation on Clear Days in Qinghai-Xizang Plateau - Min SHENG; Tsoja WANGMO; Mengmeng WANG; Yi ZHOU; Dopwang PU; Tunzhup LAGBA; Gelsor NORSANG (Gaoyuan qixiang, 2025)
Photosynthetically Active Radiation （PAR） spectrum， in visible light， is the wavelength range sensitive to plants and can be absorbed by them for photosynthesis.The characteristics of ground PAR spectrum directly affect the growth， development， morphology， physiological metabolism， yield， and adaptability of plants.In order to further understand the distribution characteristics of PAR in high-altitude areas of Xizang， this study utilized the International High-Precision Solar Spectroradiometer to conduct field observations of the PAR spectrum characteristics in the Mt.Everest， Shigatse， Lhasa， and Nyingchi regions of the Qinghai-Xizang Plateau from 2021 to 2022.The observations found that during the winter and summer solstices on the Qinghai-Xizang Plateau， the variation in PAR was significant.The peak monochromatic radiation illuminance of PAR at Mt.Everest during the summer solstice ［1251 mW·（m2·nm）-1］ to the winter solstice ［1935 mW·（m2·nm）-1］ fluctuated by up to 684 mW·（m2·nm）-1.The winter solstice integrated value of PAR spectrum at Mt.Everest （309.86 W·m-2） was 41.61% lower than the AM0 standard spectrum integrated value of PAR （530.67 W·m-2）， and 28% lower than the AM1.5 standard spectrum integrated value of PAR （429.83 W·m-2）.During the summer solstice， the PAR spectra at Mt.Everest， Shigatse， and Lhasa in Xizang all exceeded the AM1.5 standard spectrum at noon and were close to the AM0 standard spectrum.In Shigatse， Xizang， during the spring equinox and autumn equinox， the peak PAR spectra were 1699 mW·（m2·nm）-1 and 1696 mW·（m2·nm）-1 respectively， with peak values being nearly identical.This similarity is due to the same local solar altitude angle at noon （e.g.， 59.84 radians in Shigatse） during the equinoxes at the same observation point on the Tibetan Plateau， assuming other factors affecting the spectrum are the same.Comparison of observations between the Qinghai-Xizang Plateau and low-altitude areas such as Beijing， Anhui's Lu'an， and Henan's Puyang revealed that on a clear day near the winter solstice （November 20， 2021）， the integrated value of PAR spectrum at high-altitude Mt.Everest （309.86 W·m-2 was 17.19% higher than that in low-altitude Lu'an， Anhui （264.41 W·m-2）； on a clear day near the summer solstice （June 3， 2021）， the integrated value of PAR spectrum at high-altitude Mt.Everest （487.41 W·m-2） was 23.66% higher than that in low-altitude Beijing （394.15 W·m-2）； near the autumn equinox （September 19， 2021）， the integrated value of PAR spectrum in low-altitude Beijing （315.23 W·m-2） was only 71.24% of that at high-altitude Mt.Everest （442.49 W·m-2）； near the spring equinox （March 19， 2021）， the integrated value of PAR spectrum in high-altitude Shigatse （413.34 W·m-2） was 64.75% higher than that in low-altitude Puyang， Henan （261.82 W·m-2）.The results indicate that the integrated value of PAR spectrum is positively correlated with altitude， with higher altitudes corresponding to larger integrated values.Additionally， through observations of PAR spectra on clear days throughout the year， it was found that there are certain temporal variations in spectral radiation illuminance.Specifically， the spectral radiation illuminance is lowest at the winter solstice， then increases daily until reaching its peak the following year after the spring equinox， decreases daily after the summer solstice， reaches its lowest point again at the winter solstice after the autumn equinox， with the spectral radiation illuminance characteristics being basically the same during the spring equinox and autumn equinox.